On the Relevance of critical-theoretical thinking for the new system of teacher education and training in Austria: A diversity-sensitive outline of inclusive pedagogy of migration - Oberlechner, Manfred (Momentum Quarterly, 2018)
Pierre Bourdieu’s concept of education and his concept of “reflexive sociology”, Paul Mecheril’s disciplinary definition of ‘migration pedagogy’ as well as theoretical perspectives on the issues of inclusion and intersectionality lay the theoretical foundations for a line of argument, which defines the necessary conditions for an inclusive and intersectional pedagogy of migration as a key element of Austrian teacher education and training. Regarding the latter, this article defines demands for migration pedagogy regarding curricular contents, didactical processes in higher education, the personal level and the overall organization of universities. Moreover, migration pedagogy is developed further with a focus on concepts of inclusion and intersectionality and additional considerations on reflexivity in teacher education and pedagogic professions more broadly, linking it to critical theory.
Keywords: Austrian teacher education and training; pedagogy of migration; inclusion; intersectionality; diversity; reflexive habitus; critical theory